Elementary school teachers’ perceptions of the characteristics of twice-exceptional students - Alsamani, Omar Abdullah; Alsamiri, Yasir Ayed; Alfaidi, Seham Defallah (Frontiers in Education, 2023)
The current study explored the perceptions and understanding of Saudi elementary school teachers regarding the characteristics of twice-exceptional (2e) students. This qualitative phenomenological study recruited 14 elementary school teachers at schools in Medina City in Saudi Arabia. Data were gathered through in-depth semi-structured interviews to gain insight into participants’ perceptions of this student population. Findings indicated that teachers associate certain characteristics with the giftedness trait of 2e students, including excellent communication skills, problem-solving ability, strong retention, curiosity, creativity, abstract thinking, and leadership skills. Moreover, Saudi elementary school teachers perceive that 2e students experience academic challenges related to their disabilities in reading, writing, and mathematics, as well as are aware that such students tend to struggle with low self-esteem and maintaining concentration. Overall, there is a tendency to view these students as having two independent conditions—giftedness and disabilities that cause academic challenges—rather than identifying these individuals as having a single condition of being twice exceptional that comprises traits that impact their learning in combination.